Strategi Teknik Debugging untuk Sistem Operasi Windows - Herlan Wibowo; Muhamad Faisal Ilham; Elkin Rilvani (International Forum of Researchers and Lecturers, 2024)
The debugging process is a critical step in software development, especially for the Windows operating system, which offers various tools and techniques to address software issues. This study explores debugging strategies such as logging, memory analysis, real-time debugging, reverse engineering, and compilation-based techniques to identify and resolve problems such as memory leaks and unresponsive applications. Results indicate that selecting the right debugging method depends on the type and complexity of the problem, with a combination of methods often yielding the best outcomes. This study provides practical guidance for Windows users to enhance debugging effectiveness in resolving system and application issues.